(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2023)
Student governments can play an important part of the habit development of participating in democracy. A study in 2012, however, illustrated just how few students actually voted in their own student government elections. With a changing world of national politics, there is a need to understand student voting as a possible reflection of participation after college. This study compared student voting in their own government elections between 2012 and 2020, finding several, yet no significant, differences in voter turnout. The study used a sample of doctoral and comprehensive institutions, finding under one-in-five students voted in their own government elections.